DUNDRUM-D: Developmental Understanding of Drug Misuse & Dependence (Short version) - KENNEDY, HARRY (Central Mental Hospital, National Forensic Mental Health Service, 2012)
This is the short version of the Developmental Understanding of Drug Misuse and Dependence DUNDRUM-D. DUNDRUM-D is an instrument which has grown out of the series of prison psychiatric morbidity studies carried out by the National Forensic Mental Health Service in the population of the Irish Prison Service. The DUNDRUM-D is distinguished from other screening and diagnostic instruments by the developmental perspective it takes on life time careers of substance use, misuse and dependence. We recognise that those with substance misuse problems commonly begin using intoxicants such as solvents very early, typically before the age of 12 and progress through other substances as they get older and are able to access more expensive intoxicants. Some will have patterns of binge use, others are continuously intoxicated. Some will use only one or two substances of choice; others will use many different types of drug almost indiscriminately. It is not uncommon for a person to make the transition from dependence on one drug to substitution for another, followed some time later by further changes in type of intoxicant or pattern of use. All such patterns shift and change over time, and recovery is always possible. Indeed spontaneous recovery is the most common outcome for most substance misuse problems. The purpose of this form of instrument is to record these patterns as an exercise in contemplation for those who are not yet at the contemplative stage or recovery. While questions are asked about harmful use and abuse, these are deliberately reserved until towards the end of the interview. We believe the regular use of this instrument is also a way of learning from one's patients/clients. The substances used, the language, patterns and practices of use all change constantly and rapidly from month to month and from city to city. We have found that this instrument can be used in its short form as a screening tool e.g. with the SADS-L or with the CAARMS. In forensic mental health practice, it is 'substance abuse' as defined in the DSM system that is the best guide to harmful use. The form of the instrument lends itself to the assessment of other problem behaviours such as gambling, binging and purging food, and repetitive self-harm to relieve tension (e.g. cutting). The DUNDRUM-D can be used by any professionally qualified clinician.
PUBLISHED
Keywords: Drug dependence; Substance Abuse; Addiction; Mental health, instruments